Pengaruh Penambahan Octane Booster Pada Bahan Bakar Terhadap Emisi Gas Buang Kendaraan Bermotor Empat Langkah 150cc - Khambali; Syahputra, Ekasakti Hergi (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2025)
The increasing demand for motorcycles in Indonesia has contributed to rising air pollution, particularly from exhaust emissions such as CO, HC, CO₂, and O₂. This study aims to investigate the effect of adding Octane Booster to Pertamax fuel on reducing harmful emissions from 150cc four-stroke motorcycle engines. The experimental method involved adding 0.2g, 0.5g, and 1g of Octane Booster per liter of fuel and testing engine performance at 2000, 2500, 3000, and 3500 rpm using an emission analyzer. The results showed that the addition of Octane Booster significantly reduced emission levels of CO, HC, CO₂, and O₂. The most effective reduction was observed with 1g Octane Booster at 3500 rpm, where CO was reduced by 31%, HC by 34%, CO₂ by 35%, and O₂ by 33% compared to standard fuel. The study concludes that Octane Booster not only improves combustion efficiency but also contributes to lowering emissions, thereby supporting efforts to mitigate global warming and air pollution caused by motorized vehicles.